Pemberdayaan Masyarakat Untuk Menciptakan Desa Ekowisata di Wonosalam, Kabupaten Jombang - Dewa Gde Satrya; Thomas Stefanus Kaihatu; Lexi Pranata (Universitas Mathla'ul Anwar Banten, 2018)
COMMUNITY EMPOWERMENT TO CREATE ECOTOURISM VILLAGES IN WONOSALAM, JOMBANG REGENCY. Ecotourism in Wonosalam, precisely in the hamlet of Mendiro, Panglungan Village, which was developed through community service grants has the opportunity to be collaborated with agrotourism. Agro tourism consists of 5 tourist attractions: botanical gardens, plantations, food crops and horticulture, fisheries and livestock. This report is based on community service activities with the theme of creating an ecotourism village, in which the process has the opportunity to be integrated and strengthened by agrotourism destinations. In conclusion, Wonosalam can be developed into an ecotourism village destination and an agrotourism village.